EFEKTIVITAS PENGGUNAAN LEMBAR KERJA MAHASISWA TEKNIK SIPIL BERBASIS BASED LEARNING - Aisyah Dita Qanaah (CV. ADIBA AISHA AMIRA, 2023)
This research examines the effectiveness of using Student Worksheets (LKM) in Civil Engineering learning based on Project Based Learning (PjBL). With a descriptive qualitative approach, this study aims to understand the impact of using LKM on student engagement, personalization of learning, and development of critical thinking skills. The research results show that LKM increases student engagement and provides opportunities for the development of independent skills in understanding the material. However, challenges such as less conducive classroom management are also acknowledged. With a better understanding of the advantages and disadvantages of using LKM, the role of lecturers as facilitators becomes key in supporting learning effectiveness.